Patient adjusted versus health professional adjusted insulin dosing for type 2 diabetes mellitus - Ng, C.J.; Liew, S.M.; Vethakkan, S.R.; Abdullah, A.; Teng, C.L. (2013)
Diabetes mellitus is a metabolic disorder resulting from a defect in insulin secretion, insulin action, or both. A consequence of this is chronic hyperglycaemia (elevated levels of plasma glucose) with disturbances of carbohydrate, fat and protein metabolism. Long-term complications of diabetes mellitus include retinopathy, nephropathy and neuropathy, and the risk of cardiovascular disease is increased.